Il Presidente o la Presidente del Consiglio? Polemiche intorno alla scelta di Giorgia Meloni - Kadvány, Gergely (Verbum – Analecta Neolatina, 2024)
The interaction between linguistic and social change is a very important area of research in sociolinguistics. Certain elements of the language system are considered to be a reflection of social relations, when these are subject to change, their linguistic representations may also undergo changes. In turn, the language system and its use have an impact on society. In recent decades, the dynamics of this two-way interaction is evidenced in Italian morphology by the use of the gender of professional nouns, which are closely influenced by certain social transformations. To prove this, in my article I will present an extremely current case: the debate created around the choice of Giorgia Meloni, the first woman Prime Minister in Italian history, to be called il Presidente del Consiglio (masculine form). The article will show how this choice is reflected in various online newspapers and other social media platforms, confirming how changes in society can influence the linguistic system itself and how the resulting change becomes part of the accepted linguistic norm.